Botrytis cinerea B05.10 promotes disease development in Arabidopsis by suppressing WRKY33‐mediated host immunity. (17th August 2017) - Liu, Shouan; Ziegler, Jörg; Zeier, Jürgen; Birkenbihl, Rainer P.; Somssich, Imre E.
Abstract: The large WRKY transcription factor family is mainly involved in regulating plant immune responses. Arabidopsis WRKY33 is a key transcriptional regulator of hormonal and metabolic processes towards Botrytis cinerea strain 2100 infection and is essential for resistance. In contrast to B. cinerea strain 2100, the strain B05.10 is virulent on wild‐type (WT) Col‐0 Arabidopsis plants highlighting the genetic diversity within this pathogen species. We analysed how early WRKY33‐dependent responses are affected upon infection with strain B05.10 and found that most of these responses were strongly dampened during this interaction. Ectopic expression of WRKY33 resulted in complete resistance towards this strain indicating that virulence of B05.10, at least partly, depends on suppressing WRKY33 expression/protein accumulation. As a consequence, the expression levels of direct WRKY33 target genes, including those involved in the biosynthesis of camalexin, were also reduced upon infection. Concomitantly, elevated levels of the phytohormone abscisic acid (ABA) were observed. Molecular and genetic studies revealed that ABA negatively influences defence to B05.10 and effects jasmonic acid/ethylene (JA/ET) and salicylic acid (SA) levels. Susceptibility/resistance was determined by the antagonistic effect of ABA on JA, and this crosstalk required suppressing WRKY33 functions at early infection stages. This indicates that B. cinerea B05.10 promotes disease by suppressing WRKY33‐mediated host defences. Abstract : Previously, we showed that resistance of Arabidopsis thaliana Col‐0 to Botrytis cinerea strain 2100 depends on the function of the transcription factor WRKY33, and this involves not only WRKY33‐dependent activation of genes encoding enzymes of camalexin biosynthesis but also WRKY33‐mediated negative regulation of ABA biosynthesis and ABA signalling. In the current study, we tested whether the susceptibility of Col‐0 plants towards the virulent B. cinerea strain B05.10 is due to suppression of host defences involving WRKY33. Our results provide molecular and genetic evidence that B. cinerea B05.10 infection dampens induced expression of WRKY33 at early fungal infection stages and thereby subsequently mitigates several WRKY33‐mediated host immune responses. In particular, this affects camalexin biosynthesis, and the antagonist affects ABA on JA signalling.